IMPLEMENTASI DIRECT DEBIT SEBAGAI BAGIAN DARI PENERAPAN DIGITAL WALLET DALAM METODE PEMBAYARAN - Mantik, Hari (Universitas Dirgantara Marsekal Suryadarma, 2023)
AbstractDirect debit is an e-commerce payment method as part of a digital wallet which is an important phenomenon in the current Internet of things 4.0 era. How e-commerce changes marketing, how e-commerce changes financial transactions, and how e-commerce becomes an important part of people's daily lives is one of the objectives of this research. This study emphasizes how the noble direct debit implementation cycle process is from initialization, development, testing, to implementation and monitoring of direct debit products at one of the leading banks in Indonesia in collaboration with telecommunication networks as its clients. The purpose of this research is to explore the development cycle through the system development life cycle so that the strategic steps will be exposedÂ keywords: Direct Debit, e-Comerce, SDLC